Rekonstruksi Pembelajaran Bahasa Indonesia Berbasis OBE : Strategi Inovatif Penguatan Keterampilan Menulis Ilmiah Mahasiswa Universitas Muhammadiyah Maumere - Amalia Safira; Yeremias Bardi; Rubiyati Junaidin (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The development of academic writing skills among university students remains a serious challenge in higher education, particularly in Indonesian language courses that are often perceived as theoretical and procedural. This study aims to reconstruct Indonesian language learning through an Outcome Based Education (OBE) approach to strengthen students’ scientific writing skills at Universitas Muhammadiyah Maumere. Employing a qualitative research design, data were collected through classroom observations and in-depth interviews with students and lecturers over a three-week period. The findings reveal that OBE based learning encourages clearer learning objectives, increases students’ awareness of academic writing standards, and fosters reflective and critical writing practices. Students demonstrated improved understanding of scientific text structures, argument development, and academic language conventions. Furthermore, the learning process shifted from teacher centered instruction to a more participatory and student oriented model, allowing students to actively construct knowledge through observation, discussion, and writing practice. The study also highlights that the integration of contextual learning and continuous feedback plays a crucial role in enhancing students’ confidence and motivation in academic writing. These findings imply that OBE based Indonesian language instruction can serve as an effective pedagogical strategy to cultivate academic literacy, critical thinking, and responsible scholarly attitudes among university students. The study recommends broader implementation of OBE principles in language education to support sustainable improvement in higher education learning outcomes.